Coronary flow reserve during dobutamine stress in Takotsubo stress cardiomyopathy. Issue 7 (16th July 2015) - Collste, Olov; Tornvall, Per; Alam, Mahbubul; Frick, Mats
Abstract : Objectives: Takotsubo stress cardiomyopathy (TSC) is an increasingly recognised and diagnosed disease, although the underlying pathophysiology is still unknown. Our aim was to investigate the effect of the catecholamine dobutamine on coronary flow reserve (CFR) measured non-invasively in patients with TSC and controls. Our hypothesis was that dobutamine stress can induce microvascular dysfunction in patients with a previous episode of TSC. Setting: This is a case–control study and a substudy of the Stockholm Myocardial Infarction with Normal Coronaries (SMINC) study. Elective dobutamine investigations were performed focusing on non-invasive measurements of CFR. The investigations were performed more than 6 months after the acute event. Participants: 22 patients with a previous episode of TSC and 22 sex-matched and age-matched controls were recruited from the SMINC study. All patients with TSC had a previous normal cardiovascular MR investigation. Results: CFR at low-dose dobutamine was significantly lower in the TSC group compared with controls, 1.51 and 1.72, respectively (p=0.017). At high-dose dobutamine, CFR was 1.95 and 2.21 in the TSC group and controls, respectively (p=0.098). Conclusions: We could not confirm that the catecholamine dobutamine induced microvascular dysfunction in patients with TSC. However, we found a small but significant difference in CFR at low-dose dobutamine, which implies that the role of microvascular function in TSC needs to be further explored.